Analysis of Built-up Area and Land Surface Temperature Relationship in Makassar City using NDBI Processing - Setiawan, I. N.; Jumadi, J (Universitas Muhammadiyah Surakarta, 2024)
Dynamic development in Indonesia's Urban Areas is influenced by population growth, economy, and environmental dynamics. By mid-2023, Indonesia's population will reach 278,696.2 million, ranking fourth as the largest population in the world. Unbridled urban growth has resulted in urban restructuring, agricultural land transformation, and a decrease in the area of green open space. This leads to a decrease in air quality, an increase in surface temperature, as well as changes in land cover patterns. A similar pattern is seen in Makassar City, where a shortage of green open space (less than 30%) and land-to-building changes have increased the city's surface temperature. This study aims to analyze the distribution of built-up land, land surface temperature (LST) and the relationship of land change built in Makassar City from 2014 and 2023 using Landsat Imagery. Analysis using Landsat Imagery and Normalized Defference Built-up Index algorithm shows significant growth of built-up land in accordance with the development plan of Makassar City until 2026. The surface temperature classification indicates a significant increase from 2014 to 2023, which is associated with built-up land growth. The results of simple linear regression showed a positive correlation between built-up land area and surface temperature, with R Square reaching 34.7% in 2014 and 38.9% in 2023. These findings reflect the impact of development on Land Surface Temperature (LST) and emphasize the urgency of built-up land management to reduce the impact of heat in cities.